Modelling thermal loads for a non-domestic building stock: associating a priori probability with building form and construction - using building control laws and regulations. - Smith, Stefan Thor (2009)
Building Energy Assessment at stock level is an important task in identifying the best strategies for achieving a more energy efficient and low carbon society. Non-domestic buildings are identified to make up 17% of total energy consumption in England and Wales and 19% of CO2 emissions. To understand the energy requirement of the non-domestic stock, large scale (empirically based) energy surveying has been carried out namely in the Non-Domestic Building Stock project and Carbon Reductions in Buildings project.